Generations : Künstlerinnen im Dialog Part I, II, III - Goetz, Ingvild; Lencsés, Leo; Löckemann, Karsten (München : Sammlung Goetz, 2019)
Accardi, Carla ; Dash N. ; Dodd, Lucy ; Gallagher, Ellen ; Grosse, Katharina ; Guidi, Jennifer ; Holzer, Jenny ; Kasten, Barbara ; Kusama, Yayoi ; Morris, Rebecca ; Olowska, Paulina ; Rama, Carol ; Rist, Pipilotti al.
In 2018 the Sammlung Goetz is celebrating the 25th anniversary of its founding with a three-part exhibition devoted to the artistic oeuvres of women. On display will be nearly two hundred works of art, from drawings, photographs, paintings, and sculptures, to films and extensive installations by more than forty female artists, all set in an intergenerational dialogue. Besides the major artists in the Goetz Collection, such as Rosemarie Trockel, Andrea Zittel, Lucy McKenzie, Paulina Olowska, Pipilotti Rist, and Yayoi Kusama, there are also a few new (and re-) discoveries, such as the young painter Lucy Dodd, or the American nun Sister Mary Corita. The catalogue documents the three-part exhibition and also offers extensive insight into the twenty-five years of the Sammlung Goetz’s history.(from publisher)
Generations. Künstlerinnen im Dialog - Female Artists in Dialogue, PART I : Sammlung Goetz, München, 22 februar - 30 juni 2018, PART II : Haus der Kunst, München, 29 juni 2018 - 10 märz 2019, PART III : Sammlung Goetz, München, 6 dezember 2018 - 6 april 2019
boek